A Goal Programming Model for Dispatching Trucks in an Underground Gold Mine - Emdini Gliwan, Suliman; Crowe, Kevin (European Scientific Journal, ESJ, 2022)
The cost of transporting mined materials in an underground mine is major. This cost typically represents between 50 to 60 percent of a mine’s total operating costs. The problem of dispatching trucks in an underground gold mine is of major economic importance and warrants the use of a decision support model. The developments of a realistic decision-support model for the dispatching problem in an underground gold mine were addressed in this paper. The problem must address multiple conflicting objectives, and therefore, a goal programming model was formulated. The model was applied to a case study, the Red Lake underground gold mine, in Ontario, Canada. The results showed major improvements in meeting the multiple objectives of this problem versus a single objective model. The results also illustrate the flexibility that the dispatching problem (in underground gold mines) yields when solved for multiple objectives using a goal programming model.